Bean pulp bacteria package fermentation formula - HU GUOCHUN; GUO WENJIANG; LIU YANGKE; GUO JUAN (2017)
The invention relates to a bean pulp bacteria package fermentation formula, prepared from, by weight, 120-160 parts of bacillus licheniformis, 150-250 parts of bacillus subtilis, 200-300 parts of enterococcus faecium, 250-350 parts of saccharomyces cerevisiae, 600-1,000 parts of alkaline protease, 200-400 parts of acid protease, 1,300-1,600 parts of neutral protease, 1,200-1,600 parts of brown sugar powder and 400-600 parts of yeast extract powder. Fermentation by the fermented bean pulp bacteria package can get fermented bean pulp product in higher content of small peptide. 本发明涉及种发酵豆粕菌种包配方，它是由如下重量份的原料组成：地衣芽孢杆菌120-160、枯草芽孢肝菌150-250、屎肠球菌200-300、酿酒酵母250-350、碱性蛋白酶600-1000、酸性蛋白酶200-400、中性蛋白酶1300-1600、红糖粉1200-1600和酵母浸粉400-600。利用该发酵豆粕菌种包进行发酵，能够得到小肽含量较高的发酵豆粕产品。